2020
DOI: 10.1016/j.jneb.2019.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Communication With Family Child Care Providers and Feeding Preschool-Aged Children: Parental Perspectives

Abstract: Objective: To describe parent communication about child nutrition-related topics with family child care providers (FCCPs). Design: Five focus groups conducted December 2016-July 2017. Participants: Parents (n=25) of 2-to-5-year-old children attending Family Child Care Homes (FCCH) in Rhode Island. Phenomenon of interest: How and what parents communicate about with FCCPs related to feeding young children. Analysis: Recordings were transcribed verbatim. Content analysis was used to analyze transcripts by two ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…In regard to methods of communication, similar to other research providers and parents reported using various methods (Barnes et al, 2016;Mena et al, 2020). However, in this study, a third of childcare providers reported using daily sheets but fewer parents mentioned this type of communication.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In regard to methods of communication, similar to other research providers and parents reported using various methods (Barnes et al, 2016;Mena et al, 2020). However, in this study, a third of childcare providers reported using daily sheets but fewer parents mentioned this type of communication.…”
Section: Discussionsupporting
confidence: 74%
“…On the contrary, childcare providers report barriers in communicating with parents such as lack of face‐to‐face time with parents, parents prioritizing talking about food issues (e.g. food allergies) instead of nutrition in general, lack of training on communicating without conflict, and a lack of information retention from parents (Dev et al, 2017; Johnson et al, 2013; Mena et al, 2020). Ultimately, results suggest both parents and providers believe that communication with each other is important but often limited (Mena et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, FCCPs recognized the child's home environment as an important influence on children's PA and ST behaviors that can make it difficult for FCCP to engage the child in healthful activities [ 78 , 79 ]. In the current study, many FCCPs agreed that parents do not want their children to go outside when it is cold or raining, which is consistent with qualitative research findings [ 8 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, further education about appropriate beverages, screen time, feeding practices related to children's self-regulation, and communicating with parents about PA could be considered for FCCPs. Professional development offering opportunities to enhance knowledge of best practices in child nutrition, PA, and ST, as well as effective parental communication strategies to ensure consistent messages, may improve practices both in FCCHs and home environments [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the shared responsibility between parents and childcare providers for children’s health, shared communication regarding promotion of healthy eating and activity may be beneficial in supporting consistent health-related messages for young children [ 128 ]. However, communication between parents and FCCP related to preschool-aged children’s health-related behaviors remains limited [ 67 ]. Healthy Start baseline data found that over half of FCCP reported that they provided families with information about appropriate screen time behaviors for children [ 129 ], but less than 40% said that they provided families with information on PA or nutrition [ 65 , 129 ].…”
Section: Discussionmentioning
confidence: 99%